Analisis Kewajiban Zakat Madu Menurut Madzhab Abu Hanifah - Riska Amelia; Ina Nurvina Sopiana; Siti Julaiha; Lina Marlina; Ana Fauziya Diyana (STAI Al Musaddadiyah Garut, 2026)
This research aims to analyze the concept of honey zakat as an obligatory form of zakat according to the perspective of Abu Hanifah. Honey, as a productive commodity with economic value, has generated differing opinions among scholars regarding its legal status as a zakatable asset. The focus of this study is to examine the legal reasoning (istinbāṭ) employed by Abu Hanifah in determining honey as an object of zakat. The method applied in this study is library research using a qualitative approach and descriptive analysis of classical fiqh sources representing Abu Hanifah’s legal thought. The findings indicate that Abu Hanifah obligates zakat on honey through the method of qiyās (analogical reasoning), by analogizing honey to agricultural produce based on a shared effective cause (‘illah), namely its productive value and economic benefit. This determination reflects Abu Hanifah’s methodological consistency in expanding the scope of zakatable assets based on principles of justice and public welfare (maṣlaḥah). Therefore, from Abu Hanifah’s perspective, honey zakat is viewed as a form of social responsibility aligned with the objectives of Islamic law in promoting a more equitable distribution of wealth within society. Keywords: honey zakat, Abu Hanifah.